Retorika Dakwah Ustadz Koh Dennis Lim dalam Video Jama’ah Pada Heran Koh Dennis Lim Bisa Bahasa Sunda pada Media Youtube - Anni Karimah Kusnawati; Komarudin Shaleh; Muhammad Fauzi Arif (UNISBA Press, 2024)
Abstract. One of the famous da’i in Indonesia is Koh Dennis Lim, a young da’i who went viral in 2023 on social media because of his story of moving from a former bookie to a da’i, and until now, Koh Dennis is active in spreading his preaching. In his lectures, he uses polite language, parables that are easy to understand, and his attractive appearance, making Koh Dennis a favorite among millennial teenagers and mothers. The aim of the research is to find out about Koh Dennis Lim's preaching rhetoric. It is hoped that the benefits of this research can provide scientific contributions to KPI students and the wider community. Type of qualitative research, with descriptive methods. Data collection techniques use documentation and literature study methods. The research results showed that Koh Dennis provided visual contact and mental contact, characterized by providing a comprehensive view of the congregation and a response from the audience regarding what he conveyed. Pay attention to vocal exercises by using high and low speaking tones, and also use marked visual exercises when delivering the lecture, taking a sitting and standing position with a straight body. Formal clothes. Using facial expressions such as frowning, eyebrows. and use hand movemen. Abstrak. Salah satu da’i terkenal di Indonesia adalah Koh Dennis Lim, seorang pendakwah muda yang viral pada tahun 2023 di media sosial karena cerita hijrahnya dari mantan bandar judi menjadi seorang pendakwah, Dalam ceramahnya, ia menggunakan bahasa yang santun, perumpamaan-perumpamaan sehingga mudah dimengerti. Tujuan penelitian untuk mengetahui tentang retorika dakwah Koh Dennis Lim. Manfaat penelitian ini diharapkan dapat memberikan kontribusi keilmuan untuk mahasiswa KPI dan masyarakat luas. Jenis penelitian kualitatif, dengan metode Deskriptif. Teknik pengumpulan data menggunakan metode dokumentasi dan studi kepustakaan. Hasil penelitian menunjukkan Koh Dennis memberikan kontak visual dan kontak mental ditandai dengan memberikan pandangan kepada jamaah secara menyeluruh dan adanya respon dari penonton terkait apa yang ia sampaikan. Memperhatikan olah vokal dengan menggunakan tinggi rendahnya nada bicara, dan juga menggunakan olah visual ditandai saat menyampaikan ceramahnya, mengambil posisi duduk dan berdiri dengan badan tegap. Pakaian yang sopan. Menggunakan mimik wajah seperti mengerutkan kening, alis. dan menggunakan gerakan tangan.